(3Yde GdGLJeGY hGdYdhe GdGLJeGYjIs (3YdGbGJ heLGdGJ hejGOjf (B/s - (3GdahGd, UdGM eUWais ((3GdbGgQI (B:s (3YGde GdcJH,s, 1982)
(3ebOeg JegjOjI Mhd hMOI GdYdhe GdGLJeGYjI(B.s
(3HHdjhLQGajI (B: (3U(B. 255-268.s
Keywords: (3Yde GdGLJeGYs; (3GdYdhe GdGLJeGYjIs; (3Yde GdfaS GdGLJeGYjs